1985
DOI: 10.1021/j100252a023
|View full text |Cite
|
Sign up to set email alerts
|

Matrix isolation infrared spectroscopic study of the 1:1 molecular complexes between the sulfur fluorides and oxyfluorides and selected bases

Abstract: The 1:l molecular complexes between SF,, SOF2, and S02F2 with a wide variety of amines and oxygen-containing bases have been isolated and characterized in nitrogen matrices. All complexes are characterized by a red shift in the S-F stretching modes from that of the parent sulfur fluoride or oxyfluoride, as typified by the bands at 675,830, and 841 cm-' for the SF4.NH3 complex. The magnitude of these shifts to lower energy is dependent upon the strength of the base. In addition, perturbed vibrational modes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

1985
1985
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 0 publications
2
16
0
Order By: Relevance
“…Sulfur tetrafluoride SF 4 is highly reactive, and it can serve either as a Lewis acid or base. 18 The S-F stretching of SF 4 -Py or SF 4 -NH 3 complexes in a nitrogen matrix is reported to have an absorption at 841 cm −1 , and the 839 cm −1 absorption observed in the present study may be attributed to a similar complex including SF 4 . As a Lewis acid, SF 4 -Py or SF 4 -NH 3 complexes were reported in a nitrogen matrix.…”
Section: A Infrared Spectrasupporting
confidence: 55%
See 1 more Smart Citation
“…Sulfur tetrafluoride SF 4 is highly reactive, and it can serve either as a Lewis acid or base. 18 The S-F stretching of SF 4 -Py or SF 4 -NH 3 complexes in a nitrogen matrix is reported to have an absorption at 841 cm −1 , and the 839 cm −1 absorption observed in the present study may be attributed to a similar complex including SF 4 . As a Lewis acid, SF 4 -Py or SF 4 -NH 3 complexes were reported in a nitrogen matrix.…”
Section: A Infrared Spectrasupporting
confidence: 55%
“…It was shown that the A complex was produced by the photochemical reaction. The substitution of 18 O had less effect on the O-H stretching, and only the absorption of O-H in HOF at 3494 cm −1 was shifted to 3483 cm −1 , whereas the absorption at 3601 cm −1 (H-F) did not have an isotope shift. 19)], the presence of the B complex as a minor product may be possible assuming the overlapping of the spectra of A and B at 3601, 3494, 839, 822, and 673 cm −1 without showing splitting.…”
Section: B Molecular Orbital Calculationsmentioning
confidence: 89%
“…Thionyl fluoride, SOF2, serves as the link between SF4 and SO2, while sulfuryl fluoride S02F2 is a related S(VI) species. In turn, NH3 was complexed with each in inert matrices [120]. These efforts led to 1:1 complex formation in each case, as well as with methylamine, pyridine and acetone.…”
Section: Weakly Bound Complexesmentioning
confidence: 99%
“…Recently we reported the synthesis of the Lewis acid-base adduct between SF 4 and N(C 2 H 5 ) 3 and its unambiguous characterization by low-temperature Raman spectroscopy and X-ray crystallography. [1] Previous evidence for the Lewis acidity of SF 4 towardsn itrogen bases wasm ainly based on vapor pressure measurements, suggesting the existence of 1:1a dducts between SF 4 and NC 5 H 5 and N(C 2 H 5 ) 3 . [2] An elemental analysis study detected the SF 4 ·NC 5 H 5 adduct and claimed the existence of distinct SF 4 ·2 NC 5 H 5 ,S F 4 ·4 NC 5 H 5 ,a nd SF 4 ·8 NC 5 H 5 adducts at À78 8C, but no further experimental evidence has been provided for thesel atter adducts.…”
Section: Introductionmentioning
confidence: 99%
“…[3] Am atrix-isolation IR study revealed only one to three vibrational bands attributed to each of the adducts SF 4 ·NC 5 H 5 ,S F 4 ·NH 3 ,S F 4 ·CH 3 NH 2 ,a nd SF 4 ·OC(CH 3 ) 2 . [4] Extensive overlapo ft he IR bands of product and reactantp recluded definitive identification. In contrast, conclusive evidencef or the Lewis acid behavior of SF 4 towards fluoridei ons has been established by the synthesis of [N(CH 3 ) 4 ] [SF 5 ], [5] Cs [SF 5 ], [6] Rb [SF 5 ], [7] [((CH 3 ) 2 N) 3 5 ], [8] and [Cs(18crown-6) 2 ][SF 5 ].…”
Section: Introductionmentioning
confidence: 99%